Uji Efektivitas Carboxymethyl Cellulose (CMC) dan Pektin sebagai Bahan Edible Coating Buah Stroberi: Review - Elisa Fitri (Jurnal Pangan dan Gizi, 2023)
Carboxymethyl cellulose (CMC) and pectin are edible coating materials used to maintain the quality and shelf life of fruit. Strawberry is a non-climateric fruit with a short post-harvest shelf life and is easily damaged. This article aims to examine the shelf life of fruit, physical and chemical properties of fruit, to compare the effectiveness of using CMC and pectin as edible coating materials to maintain the quality and shelf life of strawberries. Articles were written in stages through a gradual library search through Publish or Perish and then continued with a more specific literature search through Google Scholar with the keywords "edible coating", "carboxymethyl cellulose (CMC)", "pectin", and "strawberry". The results of the study show that the use of CMC and pectin can increase the shelf life of fruit and reduce the rate of respiration, dehydration and spoilage in fruit. In addition, the use of CMC and pectin can also improve the physical and chemical properties of fruit, such as vitamin C content and antimicrobial activity. However, there are differences in the effectiveness of using CMC and pectin as edible coating materials depending on the type of material used. The use of CMC and pectin in the same concentration gives a different effect, pectin with a concentration of 2% has a viscosity of 238.8 cP. This value is lower than the CMC of 318.8 cP. So it can be said that CMC has greater effectiveness than pectin as an edible coating material that can improve the quality of strawberries.